Respuesta :
The solution to the equation (x + 3)2 + (x + 3) – 2 = 0 is x = -3
How to solve an equation
An equation is solved by ensuring that a whatever is operation is applied on the left-hand side, is also performed on the right-hand side.
The given equation is solved thus:
(x + 3)2 + (x + 3) – 2 = 0
Open brackets by multiplication
2x + 6 + x + 3 = 0
add similar terms
3x + 9 = 0
subtract 9 from both sides
3x = -9
divide both sides by 3
x = -3
Therefore, the solution to the equation (x + 3)2 + (x + 3) – 2 = 0 is x = -3
Learn more about solving equations at: https://brainly.com/question/22688504